The Impact of Oral Health on Respiratory Viral Infection - Akio Tada; Hidenobu Senpuku (MDPI AG, 2021)
Influenza virus and severe acute respiratory syndrome coronavirus (SARS-CoV-2) have caused respiratory diseases worldwide. Coronavirus disease 2019 (COVID-19) is now a global health concern requiring emergent measures. These viruses enter the human body through the oral cavity and infect respiratory cells. Since the oral cavity has a complex microbiota, influence of oral bacteria on respiratory virus infection is considered. Saliva has immune molecules which work as the front line in the biophylactic mechanism and has considerable influence on the incidence and progression of respiratory viral infection. Salivary scavenger molecules, such as gp340 and sialic acid, have been reported to exert anti-influenza virus activity. Salivary secretory immunoglobulin A (SIgA) has potential to acquire immunity against these viruses. Biological features of the oral cavity are thought to affect viral infection in respiratory organs in various ways. In this review, we reviewed the literature addressing the impact of oral conditions on respiratory infectious diseases caused by viruses.